Is the collaborative peer assessment model effective for genre-based writing in university? - Mazulfah Mazulfah; Abdurrachman Faridi; Dwi Rukmini; Yan Mujiyanto (International Journal of Evaluation and Research in Education (IJERE), 2023)
The existing peer assessment model for genre-based writing must be developed to gain the maximum quality of the assessment. It needs to be integrated with collaborative learning and problem-based learning and make the peer assessment as part of learning. Thus, this research has aim to determine the effectiveness of the peer assessment model in the group genre-based writing class. The method used was quantitative method with comparative design. The model was developed at seventh semester of English Education Department, Universitas Islam Negeri Salatiga, Indonesia. There are 23 pre-service English teachers (PSETs) joining on the implementation developed peer assessment model collaborative genre-based writing peer assessment model. The result revealed that there is no difference between the score from the peer assessment and the score given by the lecturer. It can be concluded that the collaborative genre-based writing peer assessment conducted by students has similarities with the assessment conducted by the teacher. It supports that the students’ and teacher’s assessment has the same quality.